THE EFFECT OF ASPECT ON GLACIATION: A CASE STUDY OF EASTERN BLACK SEA MOUNTAINS (TURKEY) - Geçen, Reşat; Toprak, Vedat; Tonbul, Saadettin (My University, 2018)
Glaciation directly depends on climate changing that developed and spread during colder temperatureperiod and shrunk during warmer period. However this changing is not uniform everywhere on earth.Beside climate properties several other conditions have effect on glaciation such as; latitude,elevation, aspect, continentality, slope, humidity etc. Especially throughout mid-latitudes the aspectbecomes more important effect on development of glaciation. Because of its location Turkey has beeninfluenced by glaciers in Pleistocene era, and many glacial landscapes have been formed throughoutthe country during this period.The aim of this study is to investigate the glaciated area in the Eastern Black Sea Mountain rangeusing Geographic Information System (GIS) technologies in order to map and evaluate severalfeatures associated with glaciers. In addition depend on aspect effect the changes on glaciated area,number and distribution of glacial landscapes on different flanks of Eastern Black Sea MountainRange is examined. Therefore the effect of aspect on glaciation is tried to be explained.The glacial shapes determined in investigation area show different properties depending on theirlocations. Generally on northern side the landscapes are more widespread than the southern. 19 of 30main valleys, 49 of 63 tributary valleys, 820 of 1222 cirques and 431 of 685 glacial lakes are locatedon northern side of the mountain chain.
Keywords: Tarih; Coğrafya; Çevre Bilimleri; Jeoloji